Blockchain-Powered Electronic Product Authenticity Verification for Global Rigorous Aura Success (M) Sdn. Bhd. - Danraj, Darven; Ramli, Sofia Najwa (Applied Information Technology And Computer Science, 2026)
Counterfeit electronic products lead to significant financial losses, erode consumer trust, and severely damage the reputations of companies worldwide. Traditional authentication methods such as QR codes, RFID tags, and AI-driven systems fail to combat sophisticated counterfeiting techniques due to vulnerabilities such as cloning, high computational demands, and limited scalability. In response, this report proposes an innovative blockchain-based solution on the Ethereum network, designed for secure and reliable product verification across complex supply chains. The system utilizes tamper-proof smart contracts, secure QR code documentation, and user engagement features, implemented with tools like Solidity, Hardhat, React, Node.js, and ethers.js. Originally developed for Global Rigorous Aura Success (M) Sdn Bhd, this adaptable solution can also be applied to industries such as pharmaceuticals, luxury goods, and automotive parts. The implementation of the system resulted in a marked reduction in counterfeit products, enhanced consumer trust through real-time product authentication, and improved operational efficiency by enabling automated and paperless record management. This solution not only addresses current counterfeiting issues but also paves the way for future innovations in product authentication and supply chain management.